2013
DOI: 10.1155/2013/689236
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of AposTherapy in Patients with Osteoarthritis of the Knee: A Two-Year Followup

Abstract: Several biomechanics treatments for knee osteoarthritis (OA) have emerged with the goal of reducing pain and improving function. Through this, researchers have hoped to achieve a transition from the pathological gait patterns to coordinated motor responses. The purpose of the study was to determine the long-term effects of a therapy using a biomechanical device in patients with knee OA. Patients with knee OA were enrolled to active and control groups. The biomechanical device used in therapy (AposTherapy) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The results suggest that most improvements occurred by 3 months, but further improvements occur between 3 and 6 months, apart from SLS in gait and MCS subscale of SF-36. This supports previous work which found that the largest improvements occurred within the initial few months of therapy and are then maintained (32). The improvements in WOMAC scores meet the OMERACT-OARSI guidelines for clinical response to treatment, signifying true positive impacts felt by patients (45).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results suggest that most improvements occurred by 3 months, but further improvements occur between 3 and 6 months, apart from SLS in gait and MCS subscale of SF-36. This supports previous work which found that the largest improvements occurred within the initial few months of therapy and are then maintained (32). The improvements in WOMAC scores meet the OMERACT-OARSI guidelines for clinical response to treatment, signifying true positive impacts felt by patients (45).…”
Section: Discussionsupporting
confidence: 88%
“…However, it reflects previous research on the therapy on different populations with similar improvements in gait and PROM's (33)(34)(35)60). Therefore, it could be assumed that the improvements can be maintained with the high compliance rates in the treatment (32). Nevertheless, future research should continue to investigate the long-term clinical effect of the treatment, in prospective, randomised control trial (RCT) design whilst tracking decay rates for joint replacement surgeries.…”
Section: Discussionmentioning
confidence: 61%
“…It must address wider perspectives of generalized neuromuscular control. In recent years, several publications regarding the effect of a novel non-invasive biomechanical device for different musculoskeletal disorders have been published [12][13][14][15]. A unique foot-worn device enables the relocation of the center of pressure [16] while training neuromuscular control [17].…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical device and treatment methodology have been previously described in depth . The biomechanical device was individually calibrated for each study participant according to his/her motion characteristics and symptoms .…”
Section: Methodsmentioning
confidence: 99%